Cultural Intelligence Integration to Teaching English for Young Learners in Curriculum Merdeka - Eti Sisviana; Bernadette Meini Lestari Malau; Buyung Zulfanio; Heru Nur Rohmat Dwi Septiyono; Agung Budi Kurniawan (Yayasan Visi Intan Permata, 2025)
This qualitative case study investigates the integration of Cultural Intelligence (CQ) into Teaching English for Young Learners (TEYL) within Indonesia’s merdeka curriculum. As the curriculum emphasizes differentiated learning and character development, CQ plays a crucial role in equipping students with the intercultural competencies necessary in the globalized world. Data were collected from 15 English teachers in public and private junior high schools in Kota Magelang, using semi-structured interviews, classroom observations, and document analysis. The findings reveal that although many teachers intuitively apply aspects of CQ, its implementation remains inconsistent due to the limited curriculum guidance, lack of professional training, and insufficient resources. Teachers identified key benefits, including improved communication, empathy, and global awareness. The study recommends the explicit integration of CQ frameworks into curriculum design and teacher training programs. By systematically embedding CQ into TEYL, merdeka curriculum can cultivate culturally competent, empathetic, and globally minded students from an early age.